(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Plant organisms actively respond to changes in the natural components of their environment. A sensitive indicator of the adaptation of the plant organism to the environment is the state of the reproductive system. The article discusses the results of a study of the sex composition of populations and the quality of pollen grains of two species of the genus Salix. The peculiarities of the sexual sphere Salix fragilis and Salix dasyclados revealed during the work show the feminizing effect on the sexual structure of the populations of these types of anthropogenic factors. During the increase of stress conditions the level of vitality and fertilizing ability of pollen grains decreases. The results of the study confirm the possibility of using these plants as bioindicators of the environment.